Respuesta :
Answer: x= -1
Step-by-step explanation: 6x = 2x-4 4x= -4 and x=-1
From the given statement the unknown number is found to be - 1
The given statements can written in algebraic form as follows;
the unknown number = x
the number is multiplied by 6 = 6x
four less than twice the same number = 2x - 4
then, from the given statement the final equation equation becomes;
6x = 2x - 4
This unknown number can be solved by collecting similar terms together;
6x - 2x = -4
4x = -4
divide through by 4
[tex]\frac{4x}{4} = \frac{-4}{4} \\\\x = -1[/tex]
Thus, the unknown number is - 1
Learn more here: https://brainly.com/question/24369824